Research handbook on human rights and poverty - Davis, Martha F. 1957-; Kjaerum, Morten; Lyons, Amanda (Research handbooks in human rights, 2023)
"This important Research Handbook explores the nexus between human rights, poverty and inequality as a critical lens for understanding and addressing key challenges of the coming decades, including the objectives set out in the Sustainable Development Goals. The Research Handbook starts from the premise that poverty is not solely an issue of minimum income and explores the profound ways that deprivation and distributive inequality of power and capability relate to economic, social, cultural, civil and political rights."